A new large-flowered species of Telipogon (Orchidaceae) discovered in Peru - Kolanowska, Marta; Szlachetko, Dariusz L. (Phytotaxa, 2025)
A new species of Telipogon from montane cloud forests of Peru is described and illustrated. Plants of this species grow at an elevation of over 3000 meters and are characterized by a reniform, basally papillate lip, ornamented with a distinctive triangular-ovate callus that is partially free from the lip disc, with thickened areas on either side of the callus spreading toward the lip margins and resembling wings. The new species resembles Ecuadorian T. frymirei but differs in having petals that are almost as wide as long, as well as in lip shape and venation.